PENGARUH PIJAT RELAKSASI TERHADAP PENURUNAN SAKIT KEPALA PADA IBU HAMIL TRIMESTER I - nicky danur jayanti (LPPMK STIKES Widyagama Husada, 2019)
Headache is a diffuse pain in various parts of the head which varies in its intensity, and the duration of which is a neurological complaint during pregnancy, to reduce headaches by providing provision of drug therapy from aroma therapy, relaxation massage, hot and cold compresses. A relaxing massage is given to ease the discomfort, maintain the overall function of the body and provide emotional support. The study aimed to find out if there is an effect of a relaxation massage in decreasing headaches in pregnant women trimester I.The research method used was a comparative study using a pre-test and post-test group design. The samples used were 15 pregnant women who fit the inclusion criteria and population as many as 19 respondents. The sampling technique used was purposive sampling. Analysis of the results of research was using the Wilcoxon test analysis. Most of the first trimester pregnant women have headaches prior to the relaxation massage were 10 respondents (66.7%), relaxation massage after having a mild headache were 11 respondents (73.3%). Based on the analysis of Wilcoxon test obtained value ρ = 0.002, thus it is said that Ha is accepted because ρ <0.05 means that there is an effect of the level of head pain in the first trimester pregnant women before and after a relaxing massage treatment. It is advised to pregnant women, to add motivation to deal with headaches naturally.